Symmetric duality in complex spaces over cones - Ahmad, Izhar; Agarwal, Divya; Gupta, Shiv Kumar (Yugoslav Journal of Operations Research, 2021)
Duality theory plays an important role in optimization theory. It has been extensively used for many theoretical and computational problems in mathematical programming. In this paper duality results are established for first and second order Wolfe and Mond-Weir type symmetric dual programs over general polyhedral cones in complex spaces. Corresponding duality relations for nondifferentiable case are also stated. This work will also remove inconsistencies in the earlier work from the literature.